El Thawra and El Balad: narratives of youth about protest participation and political subjectivity in the January 25 Revolution - Galal, Ola (AUC Knowledge Fountain, 2013)
This thesis documents the narratives of a group of Egyptian youth about their participation in the 18 days of protest and analyzes their narratives in terms of reasons and meanings of taking part in such events. First, I analyze how these youth constructed their memory of the 18 days and produced a certain version of history. Second, I look at the meanings they ascribed to the Revolution through examining their narratives about why and how they participated in the 18 days and how such an experience changed their perception about and their desire for participating in collective action and politics in general. Analytically, I examine the making of political subjects through the unfolding of an event, i.e. the Revolution. I argue that the making of political subjectivity through participation in the events identified as the Revolution is equally shaped by sensibilities of belonging to a collective articulated in patriotic terms. In sum, I aim to contribute to the production of histories about the Revolution from the perspective of its participants, as well as to analyze the meanings of belonging, the nation, citizenship, and subjectivity that emerge from experiences of protest and the constitution of narratives thereof. I contend that it is not only the events themselves and the experiences thereof that shape political subjectivity, but equally important is the production of historical narratives thereof.